Pengaruh Earnings Performance Terhadap Cumulative Abnormal Return dengan Internal Control sebagai Variabel Moderasi - Grecia Hotroha; Einde Evana (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
Earnings performance is seen as one of the main indicators in assessing the company's financial performance, which can influence investor decisions and be reflected in market reactions through abnormal returns. Meanwhile, internal control is considered as an internal control mechanism that can strengthen investor confidence in the quality of earnings information submitted by the company. This study aims to examine the effect of earnings performance on cumulative abnormal return (CAR) and the role of internal control as a moderating variable in the relationship. The focus of this research is on real estate and property sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The sample of this study consisted of 44 companies and 199 observations selected through purposive sampling technique with certain criteria. Hypothesis testing was carried out using moderated regression analysis. The results showed that earnings performance has a positive and significant effect on cumulative abnormal return, which indicates that the better the company's earnings performance, the higher the positive market reaction to the information. In addition, other findings show that internal control moderates positively and significantly the relationship between earnings performance and cumulative abnormal return. This means that the effect of earnings performance on CAR will be stronger in companies that have a good internal control system.